Perkembangan Dakwah di Capetown, Afrika Selatan dan Survivalnya Masa Kini - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1999)
There were very few Muslims in Malay Archipelago a decade ago who knew about the da’wah in Cape Town. Just after that, the knowledge of it began to spread, especially among the Islamic community in Malaysia, as a result of the effective communication nowadays. This article consists of two parts (part I and part II). In part I, it discusses several Muslims who had been taken mostly from the Malay Archipelago and India to Cape Town since the 1650’s. It describes their excellent efforts in building da’wah history in Cape Town. This article also focuses the condition of the da’wah in Cape Town today and the problems of Muslims community in it.